Large, regionally variable shifts in diatom and dinoflagellate biomass in the North Atlantic over six decades - Crispin M. Mutshinda; Zoe V. Finkel; Andrew J. Irwin (PLoS ONE, 2025)
The North Atlantic Ocean has large seasonal blooms rich in diatoms and dinoflagellates which can contribute disproportionately relative to other primary producers to export production and transfer of resources up the food web. Here we analyze data from the Continuous Plankton Recorder to reconstruct variation in the surface ocean diatom and dinoflagellate community biomass over 6 decades across the North Atlantic. We find: 1) diatom and dinoflagellate biomass has decreased up to 2% per year throughout the North Atlantic except in the eastern and western shelf regions, and 2) there has been a 1–2% per year increase in diatom biomass relative to total diatom and dinoflagellate biomass throughout the North Atlantic, except the Arctic province, from 1960–2017. Our results confirm the widely reported relationship where diatoms are displaced by dinoflagellates as waters warm on monthly to annual time scales. The common assumption that gradual ocean warming will result in a decadal-scale shift from diatoms to dinoflagellates was not supported by our analysis. Predicting the effects of climate change likely requires consideration of the consequences for the whole community, the simultaneous change of multiple environmental variables, and the evolutionary potential of plankton populations.